Altered Intestinal Microbiomes and Lipid Metabolism in Patients With Prolonged Disorders of Consciousness - Yu, Jie; Cheng, Qisheng; He, Fangping; Meng, Fanxia; Yu, Yamei; Xu, Chuan; Wen, Xinrui; Hong, Lirong; Gao, Jian; Li, Jingqi; Pan, Gang; Li, Ming D.; et al. (Frontiers in Immunology, 2022)
Intestinal microbiotas regulate brain function of the host through the production of a myriad of metabolites and are associated with various neurological diseases. Understanding intestinal microbiome of patients in chronic disorders of consciousness (DoC) is important for the evaluation and treatment of the disease. To investigate the difference of intestinal microbiome and short-chain fatty acids (SCFAs) among the patients in vegetative state (VS), minimally conscious state (MCS) and emerged from minimally conscious state (EMCS), as well as the influence of antibiotics on these patients, 16S rRNA sequencing and targeted lipidomics were performed on their fecal samples and electroencephalogram (EEG) signals analysis were used to evaluate their brain function. Our results showed that intestinal microbiome among the three groups differed greatly and some microbial community with its production of SCFAs were reduced in VS patients compared to the other two groups. Moreover, reduced microbial communities and five major SCFAs along with attenuated brain functional connectivity were observed in MCS patients treated with antibiotics compared to those received no antibiotic treatment, but not in the other pairwise comparisons. Finally, three genera level of microbiota, Faecailbacterium, Enterococcus and Methanobrevibacter, were considered as potential biomarkers to distinguish patients in MCS from VS with high accuracy both in the discovery cohorts and validation cohorts. Together, our findings improved the understanding of patients with chronic DoC from intestinal microbiome and provided a new reference for therapeutic targets exploration.